Digital Agent's Engagement and Affective Posture Impact Its Social Presence and Trustworthiness in Group Decision-Making - Han, Bin; Kim, Hanseob; Kim, Jieun; Syawaludin, Muhammad Firdaus; Hwang, Jae-In (2023 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2023)
This poster introduces a user study investigating whether a digital agent's engagement and affective posture in a group decision-making scenario influence how users perceive the digital agent's social presence and trustworthiness. Our experiment was conducted with a three-person group discussion with two participants and one digital agent, and a 2 × 2 within-subject study manipulating the engagement and affective posture of a digital agent. Our findings indicate that during group discussions, the engagement posture of digital agents positively affected user perception of digital agents, whereas their affective posture negatively affected user perception.